Historical and historiographical dialogues: 19th and 20 th centuries - Naxara, Marcia [UNESP] (Sociedade Brasileria de Teoria e Historia de Historiografia, 2013)
In this paper, I try to juxtapose the historiographical perspectives of two authors - Henrique de Beaurepaire-Rohan (1812-1894) and Manoel Luiz Salgado Guimarães (1952-2010). In spite of being intellectuals whose lives were separated by more than a century, both had strong interests on knowledge about the writing Brazil's history. For Beaurepaire-Rohan, cultivating knowledge of Brazil's geographical and historical constitution was needed for the larger task of constructing the nation. Guimarães, on his side, used to dedicate special attention to the study of historiographical procedures and to understanding the debates around the issue of how to write history from a national point of view in nineteenth-century Brazil. The paper is thus an exercise in approaching and distancing the aims of today's historians to/from those of their nineteenth- -century counterparts.
Diálogos históricos e historiográficos: séculos XIX e XX
Keywords: Henrique de Beaurepaire-Rohan; Historiography; Manoel Luiz Salgado Guimarães